STRATEGIES FOR DEVELOPING GREEN FINANCIAL INSTRUMENTS IN THE UZBEKISTAN ECONOMY - Alikulov Mekhmonali Salahiddin ugli (Scholar Express Journals, 2025)
The article studies the views of leading scientists from around the world on strategies for developing green financial instruments in the economy of Uzbekistan, analyzes the main types of green financial instruments and their functions, develops the stages of the strategy for developing green financial instruments in Uzbekistan based on international standards, develops proposals on the topic, and gives recommendations for their application in our country
Keywords: Green economy; green sukuk; environmental insurance